PENGUATAN LITERASI POLITIK MASYARAKAT DI DESA HUNTU BARAT KABUPATEN BONE BOLANGO - Saleh Al Hamid; Sastro Mustapa Wantu; Udin Hamim (Universitas Bina Taruna Gorontalo, 2023)
This Community Service (PkM) aims to increase people's political awareness through the spirit of political literacy and provide new initiatives for improving the quality of democracy at the village level. The method used is interactive dialogue in the form of discussions discussing the topic of strengthening and empowering people's political knowledge through sustainable political education so that the quality of democracy is not eroded by the bad effects of hoaxes, involving lecturers, students and the village government. The dialogue process involves resource persons including lecturers and also the audience (invitees from elements of the village government) to respond to the contents of the dialog being discussed. The expected result of this PkM is to make political literacy a new culture in the people of Huntu Barat Village which can be channeled through sustainable political education. Democracy will not be sufficient only to be built from above, but must also be endeavored from below (grass root), namely through society as the subject as well as the object of democracy. Therefore, increasing the knowledge and ability of the people's political literacy will slowly create a healthy and quality democratic climate. This PkM activity was attended by 100 participants from both the general public and students as well as several lecturers from the Faculty of Social Sciences, State University of Gorontalo.